Establishment of land easements for the needs of the energy industry: scientific and practical legal problems - Kharytonova, T. E.; Shcherbakov, Y. S. (Науковий вісник Ужгородського національного університету. Серія Право, 2025)
The article examines the scientific and practical problems of establishing land easements for the needs of the energy industry in Ukraine based on the analysis of current legislation, modern doctrine and current judicial practice. The conclusions are drawn that the legislator actively applies a utilitarian approach to the formation of legislative support for easement relations. This leads to a departure from traditional theoretical canons and the formation of a hybrid type of land easements, which combine the features of both predial (real) and personal easements, while forming a new type of relationship. Such easements are established in favor of certain interested parties, which are, in particular, energy enterprises, for the construction, placement, repair of linear objects of energy infrastructure. In contrast to classic personal easements, the aforementioned hybrid easements are legally tied to property – to those linear energy infrastructure facilities that served as the reason for establishing easements. This approach simplifies the procedure for re-registration of land easements in the event of the transfer of ownership rights to such energy facilities, which is generally aimed at meeting the needs for stable energy supply without unnecessary bureaucratic obstacles. The same goal – simplification of land-easement relations for energy enterprises – is pursued by other numerous changes made to land legislation over the past few years. At the same time, utilitarianism, which becomes the main motive and methodological technique of the lawmaker on the path to improving the analyzed legislation, does not turn easement into a solid dominant over property rights. A significant safeguard against possible violations remains a judicial appeal. The specificity of land-easement relations lies in the need to study and evaluate each specific case for the possibility and legality of establishing such a right. At the same time, these relations are significantly complicated by the need to take into account the public and legal interests of the energy industry, especially in the context of military operations and post-war reconstruction of the country.